2006
DOI: 10.1149/1.2200156
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Properties of Oxide Films on Platinum

Abstract: Electrocatalysts supporting the oxygen electrode reaction are commonly covered with thin oxide films that may have a profound influence over the kinetics of the reaction. Little is currently known about the role of oxide films on electrocatalysts, particularly with regard to the role of the defect structure. In this work, the physical and defect structures of the oxide film that forms on platinum in 0.5M normalH2SO4 under steady-state conditions have been investigated using electrochemical impedance spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 65 publications
6
93
1
Order By: Relevance
“…MottSchottky analysis based on impedance measurements is a powerful in situ technique for assessing the electronic properties of the passive film. It has been used successfully in the past for the characterization of passive films formed on different passive materials [37,40,64]. According to semiconductor physical theory, the Mott-Schottky relationship expressing the potential dependence of the space charge capacitance C sc of a semiconductor film under depletion condition is described by Eq.…”
Section: Influence Of Nb Addition On the Electronic Properties Of Pasmentioning
confidence: 99%
“…MottSchottky analysis based on impedance measurements is a powerful in situ technique for assessing the electronic properties of the passive film. It has been used successfully in the past for the characterization of passive films formed on different passive materials [37,40,64]. According to semiconductor physical theory, the Mott-Schottky relationship expressing the potential dependence of the space charge capacitance C sc of a semiconductor film under depletion condition is described by Eq.…”
Section: Influence Of Nb Addition On the Electronic Properties Of Pasmentioning
confidence: 99%
“…In addition, based on the in-situ electrochemical scanning tunneling microscopy (STM) observation, Wakisaka et al [23] have found that the irreversible morphological changes at Pt(111) occur predominantly during the reduction phase of oxide. The underlying process is sensitive to the formation of the socalled as α-oxide phase [24] that forms as a surface layer upon ramping up the potential to values above ∼1.1 V RHE [11].…”
Section: Introductionmentioning
confidence: 99%
“…9,11) Saturation may be attributed to the growth of the Pt oxide as the potential increases. 16,17) Above 1.55 V, the I C increased with E W to 1.75 V, after which it decreased. Thus, the initiation of the OER triggered the dissolution of Pt 4+ .…”
Section: +mentioning
confidence: 93%
“…(4)), the interfacial place exchange of the adsorbed oxygen atoms with the top layer of the Pt atoms, and the formation of PtO 2 (eq. (5)), 13,16,17) as represented by the I W in the inset of Fig. 6(a).…”
Section: +mentioning
confidence: 99%